. (December 2014) - Takach, Geo
This article (re)presents views attacking and defending critical, arts-based rejoinders to neoliberal policies and pedagogy that preserve the naturalized, hegemonic privileges of a relative few at the expense of broader society. Drawing on the author's experiences as an arts-based researcher, instructor, and media commentator, this work is framed satirically as the transcript of a fictionalized phone-in radio show, Ticked Talk Radio. Abetted by a host of debatable neutrality, a guest ranter squelches Finley's clarion call for critical, arts-based inquiry, pedagogy, and performance. The guest's views are challenged by callers channeling leading arts-based and critical researchers and thinkers. As the callers are swatted aside, they resort to increasingly radical measures, prompting the station to import security reinforcements from the ranks of students. By sign-off, the host and guest cling to an assumed victory, but unanticipated developments threaten to unseat them.